Regulation mechanism of long non-coding RNA in plant secondary metabolite biosynthesis - Yuting LI; Huan HAN; Jiabao YE; Feng XU; Weiwei ZHANG; Yongling LIAO (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2022)
Long non-coding RNAs (lncRNAs) are widely available transcription products of more than 200 nucleotides with unrecognizable coding potential. A large number of lncRNAs have been identified in different plants. lncRNAs are involved in various basic biological processes at the transcriptional, post-transcriptional and epigenetic levels as key regulatory molecules, including in the regulation of flowering time and reproductive organ morphogenesis, and they play important roles in the biosynthesis of plant secondary metabolites. In this paper, we review the research strategies of lncRNAs and lncRNAs related to the biosynthesis of plant secondary metabolites, focusing on the research strategies for studying lncRNAs and the effects of lncRNAs on the biosynthesis of terpenoids, alkaloids and flavonoids, aiming to provide new ideas for the study of the regulation of plant secondary metabolite biosynthesis.